2019
DOI: 10.1371/journal.pbio.3000189
|View full text |Cite
|
Sign up to set email alerts
|

Ablating astrocyte insulin receptors leads to delayed puberty and hypogonadism in mice

Abstract: Insulin resistance and obesity are associated with reduced gonadotropin-releasing hormone (GnRH) release and infertility. Mice that lack insulin receptors (IRs) throughout development in both neuronal and non-neuronal brain cells are known to exhibit subfertility due to hypogonadotropic hypogonadism. However, attempts to recapitulate this phenotype by targeting specific neurons have failed. To determine whether astrocytic insulin sensing plays a role in the regulation of fertility, we generated mice lacking IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 92 publications
2
21
0
Order By: Relevance
“…A second hormone, namely insulin, also acts directly on astrocytes and deletion of insulin receptors from astrocytes causes reproductive dysfunction in mice. Astrocytes in these animals show lower levels of PGE2 than wild‐type controls, suggesting that insulin acts on hypothalamic astrocytes to stimulate GnRH neurones via PGE2 gliotransmission . PGE2 also negatively regulates synaptic input to GnRH neurones in an activity‐dependent manner, suggesting that astrocytes can decrease GnRH neuronal firing .…”
Section: Astrocytes and The Neuroendocrine Regulation Of Reproductivementioning
confidence: 93%
“…A second hormone, namely insulin, also acts directly on astrocytes and deletion of insulin receptors from astrocytes causes reproductive dysfunction in mice. Astrocytes in these animals show lower levels of PGE2 than wild‐type controls, suggesting that insulin acts on hypothalamic astrocytes to stimulate GnRH neurones via PGE2 gliotransmission . PGE2 also negatively regulates synaptic input to GnRH neurones in an activity‐dependent manner, suggesting that astrocytes can decrease GnRH neuronal firing .…”
Section: Astrocytes and The Neuroendocrine Regulation Of Reproductivementioning
confidence: 93%
“…95 Very recently, we demonstrated that mice lacking Insr in astrocytes exhibited delayed puberty, irregular and lengthened oestrous cycles, low gonadotrophin and sex steroid levels, impaired spermatogenesis and ovarian follicle maturation, and subfertility. 96 These findings demonstrate that insulin sensing by astrocytes, unlike the neuronal populations studied to date, is indispensable for the function of the reproductive axis even under normal dietary conditions.…”
Section: Astroglial Cellsmentioning
confidence: 79%
“…Biochemical analyses requiring cell lysis are limited by the fact that they do not discriminate between insulin receptor derived from neurons or non‐neuronal cells. Insulin has been shown to exercise effects through activation of astrocytical insulin receptor in several brain regions (Cai et al, 2018; Garcia‐Caceres et al, 2016; Manaserh et al, 2019), whereas the immediate downstream effects of insulin on neurons are more difficult to define (Boyd et al, 1985; Duarte et al, 2006; Werner et al, 1989). It is therefore important to show in any model that the insulin receptor is present in neurons, as we have done here for our dissociated hippocampal cultures.…”
Section: Discussionmentioning
confidence: 99%